The Effect Ethnic on Poverty in DIY Province - Purnomo, Sodik Dwi; Istiqomah, Istiqomah; Suharno, Suharno (Universitas Negeri Semarang, 2020)
The Special Province of Yogyakarta does not to allow non-native Indonesian citizens residing in the Province of DIY to possess land titles. This study aims to analyze the effect of ethnic discrimination on poverty by adding control variables such as working capital credit, investment credit, economic and education infrastructure. It employs time series data in the period 2000-2018 and are analyzed using multiple linear regression with ordinary least Square (OLS) model. The results show that working capital credit and investment credit have a negative and significant effect on poverty.Ã‚Â Ethnicity has a positive and significant effect on poverty. Education infrastructure has a significant effect on poverty. The findings imply the need for a review of the policy on the prohibition of land ownership and the need for the performance of the banking sector in the form of lending as well as the need to support human resources improvement through improving educational infrastructure and promotingÃ‚Â the quality of teachers in reducing the number of poor people.